Immunotherapeutic Potential of Mollusk Hemocyanins in Combination with Human Vaccine Adjuvants in Murine Models of Oral Cancer - Juan José Mora Román; Miguel Del Campo; Javiera Villar; Francesca Paolini; Gianfranca Curzio; Aldo Venuti; Lilian Jara; Jorge Ferreira; Paola Murgas; Alvaro Lladser; Augusto Manubens; María Inés Becker (Journal of Immunology Research)
Mollusk hemocyanins have been used for decades in immunological and clinical applications as natural, nontoxic, nonpathogenic, and nonspecific immunostimulants for the treatment of superficial bladder cancer, as carriers/adjuvants of tumor-associated antigens in cancer vaccine development and as adjuvants to dendritic cell-based immunotherapy, because these glycoproteins induce a bias towards Th1 immunity. Here, we analyzed the preclinical therapeutic potential of the traditional keyhole limpet hemocyanin (KLH) and two new hemocyanins from Concholepas concholepas (CCH) and Fissurella latimarginata (FLH) in mouse models of oral squamous cell carcinoma. Due to the aggressiveness and deadly malignant potential of this cancer, the hemocyanins were applied in combination with adjuvants, such as alum, AddaVax, and QS-21, which have been shown to be safe and effective in human vaccines, to potentiate their antitumor activity. The immunogenic performance of the hemocyanins in combination with the adjuvants was compared, and the best formulation was evaluated for its antitumor effects in two murine models of oral cancer: MOC7 cells implanted in the flank (heterotopic) and bioluminescent AT-84 E7 Luc cells implanted in the floor of the mouth (orthotopic). The results demonstrated that the hemocyanins in combination with QS-21 showed the greatest immunogenicity, as reflected by a robust, specific humoral response predominantly characterized by IgG2a antibodies and a sustained cellular response manifesting as a delayed hypersensitivity reaction. The KLH- and FLH-QS-21 formulations showed reduced tumor development and greater overall survival. Hemocyanins, as opposed to QS-21, had no cytotoxic effect on either oral cancer cell line cultured in vitro, supporting the idea that the antitumor effects of hemocyanins are associated with their modulation of the immune response. Therefore, hemocyanin utilization would allow a lower QS-21 dosage to achieve therapeutic results. Overall, our study opens a new door to further investigation of the use of hemocyanins plus adjuvants for the development of immunotherapies against oral carcinoma.